Thyroid hormone resistance misdiagnosed as Graves' disease - Manish Gutch; Annesh Bhattacharya; Sukriti Kumar; Syed Mohd Razi; Rao Somendra Singh; Rajendra Kumar Pahan (Wolters Kluwer Medknow Publications, 2017)
Resistance to thyroid hormone (RTH) syndrome is a very rare disorder characterized by mutations of the thyroid hormone receptor beta and is usually inherited as an autosomal dominant trait. Patients with RTH are usually euthyroid but rarely may present with signs and symptoms consistent with hyperthyroidism. Here, we describe the case of a young girl with goiter who was previously misdiagnosed to have hyperthyroidism and was subsequently diagnosed to be suffering from RTH.